Дослідження іоноселективних електродів для вимірювання концентрації мінеральних елементів у живильному розчині - Синявський, О. Ю.; Савченко, В. В. (Energy and Automation, 2017)
RESEARCH OF ION-SOLID ELECTRODES FOR MEASURING THE CONCENTRATION OF MINERAL ELEMENTS IN THE LIVING SOLUTIONA. Sinyavsky, V.V. Savchenko The most important factors in the hydroponic cultivation of plants are acidity (pH) and the concentration of mineral elements in the nutrient solution, which should be maintained at an optimal level during the entire period of vegetation.Currently, adjustments of nutrient solutions are made on the basis of chemical analyzes performed by the agrochemical laboratory.General defects of devices based on optical methods of analysis are insufficient for agrochemical analysis of measurement efficiency, high labor costs for preparation of samples and processing of measurement results, constructive complexity, which determines the high cost of machinery and as a consequence of high cost of analysis. In addition, the discreteness of sampling does not allow for continuous monitoring of changes in the parameters of the nutrient solution and timely to make adjustments.In connection with this, there was a need for the development of equipment that provides automatic control of the concentration of mineral elements in the nutrient solution.The purpose of the study is to establish the possibility of using ion-selective electrodes to determine the concentration of mineral elements in nourishing solutions.Since the nutrient solution is a multicomponent solution, it was necessary to study the selectivity of the electrodes in all the major ions that are in the solution.Determination of the selectivity of electrodes in nutrient solutions was carried out using the theory of experiment planning.For the significance of the factors taken into account the concentration of ions that are part of nutrient solutions: ammonium, potassium, sodium, calcium, magnesium, nitrate, phosphate, sulfate and chloride ions. For the values of the upper level of the factor the maximum concentration of ions in solutions was taken, for the values of the lower level - the minimum concentration.The potential of ion-selective electrodes depends on the temperature, the change of which causes a change in the oscillation of the electrode function:The dependence of the potentials of the ion-selective electrodes on the temperature was removed when placed in a Zonneveld’s solution for tomatoes. The temperature of the solution was changed within 10 - 50 °С. In this case, the values of the potentials for each type of electrodes studied were measured.In the study of the drift of the standard potential of the electrodes, they were stirred in a Zonneveld’s solution for tomatoes. The temperature of the solution was maintained at a constant temperature of 20 °С. The iodine points of the electrodes were measured during the day in one hour. The studies were conducted within a month.In determining the response time using a recording potentiometer, the dependence of the EMF on the time when the electrode was transferred into the test solution from the storage solutions and distilled water was recorded. The concentration of solutions was 10-3 and 10-1 mol / dm3; temperature – 20 °С.The conducted studies have shown that the potentials of nitrate, potassium, calcium and chloride electrodes in nutrient solutions depend on the concentration of only the potential determinant ions.The potential of the ammonium ion-selective electrode depends on both the activity of the ammonium ions and, in part, on the concentration of potassium ions. The coefficient of selectivity of ammonium electrode to potassium ion is 0.1.The glass electrode, which is used to determine the concentration of potassium ions, has insufficient selectivity in relation to ammonium ions. According to experimental data, a selectivity factor of 0.2 was determined.The electrode for determining the water hardness has the same selectivity for calcium and magnesium ions.The dependence of the electrode potential introduced in the Zonneveld’s nutritional solution on the temperature of the solid-contact electrodes is linear in nature. According to experimental data, the coefficient of temperature correction was determined, which is at the measured concentrations of monovalent ions of 0.2 mV/K·pX,  dual-valued ions - 0.1 mV/ K·pX.Ion-selective electrodes with a liquid membrane have a significant drift of the standard potential, which during the month reaches 15 mV. During the working day it does not exceed 1 mV. The change in the potentials of solid contact electrodes during a month does not exceed 5 mV. Solid contact electrodes are characterized by a much greater stability of the electrodes' potentials than electrodes with liquid contact.The smallest response time is observed when the electrode is transferred from distilled water into a nutrient solution (1.5-12.0 sec). Response time when the electrode is transferred to the nutrient solution from the storage solution 10-1 M for electrodes with a liquid contact reaches 2.5 min, and for solid-contact electrodes does not exceed 1 min.ConclusionsThe conducted studies of metrological characteristics of ion-selective electrodes have shown that they can be used in systems of automatic control of the concentration of ammonium and nitrate nitrogen, potassium, calcium, magnesium, sodium, chloride in nutrient solutions. Advantages have electrodes with firm contact, because they have less drift potential and time of its installation.